Mission-based marketing : positioning your not-for-profit in an increasingly competitive world - Brinckerhoff, Peter C., 1952- (Hoboken, N.J. : John Wiley & Sons, 2010)
A direct, practical guide revealing how you can lead your not-for-profit to success through mission-based marketing. Now in a Third Edition, Mission-Based Marketing is a direct, practical guide showing how you can lead your not-for-profit to success in a more competitive world. This book provides the knowledge and skills you need to build a market-driven organization that holds onto its core values, does a better job of providing mission, and successfully competes for funding, clients, referral sources, staff, and board members.: Includes new material on nonprofit websites, social networking a.
Mission-Based Marketing, Third Edition: Positioning Your Not-for-Profit in an Increasingly Competitive World; Contents; About the Author; Chapter 1: Introduction; Chapter 2: Marketing: A Key to Better Mission; Chapter 3: Being Mission Based and Market Driven; Chapter 4: Being Flexible and Innovating with the Market; Chapter 5: The Marketing Cycle for a Nonprofit; Chapter 6: Who Are Your Markets?; Chapter 7: Who Are Your Competitors?; Chapter 8: Asking Your Markets What They Want; Chapter 9: Better Marketing Materials; Chapter 10: Technology and Marketing.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Nonprofit organizations -- Marketing; Marketing; Marketing; Associations sans but lucratif -- Marketing; Marketing; marketing; BUSINESS & ECONOMICS -- Distribution; BUSINESS & ECONOMICS -- Marketing -- General; Marketing; Nonprofit organizations -- Marketing